Bauran Pemasaran (4P) Pada Produk Minyak Kelapa Kampung “Lanarasa” Di Desa Tambu Kecamatan Balaesang - Lilis R. Dihuma; Muhammad Din; Faruq Lamusa (Transformasi: Journal of Economics and Business Management, 2023)
Coconut is a plant that has a high economy because all parts of the coconut plant can be used for human interests, therefore the coconut plant is also called the tree of human life. Donggala Regency is one of the coconut centers in Central Sulawesi Province that has the potential for natural resources in supporting the development of coconut farming businesses where in Tambu village the coconut itself is processed into virgin coconut oil. The purpose of this community service is to provide an understanding and application of the marketing mix, namely products, prices, places, and promotions to Lanarasa coconut oil products. The benefits of this activity are expected to understand more about the marketing mix can help the Lanarasa coconut oil production process in the future to be good. The method carried out is Observation and mentoring. The result achieved is that the public better understands the application of the marketing mix to Lanarasa products. Lanarasa is a brand name product with an affordable market price offered but has good quality.and also has a strategic production place and close to raw materials so as to facilitate the production process. For promotions so far, we market products both directly and also through social media.